Birds Of Prey: Revealing Harley’s Behavior Exercise Her Agency - Haya Latul Qodarain (LITERA KULTURA : Journal of Literary and Cultural Studies, 2021)
The injustice toward women in society affected the work of women’s agency. Some studies believe that women are easier to get injustice in society use to the stereotyping between men and women. The domination of men in society putting them in higher level than women. Women’s agency doesn’t depict well in society that is why women are fighting more to get back their agency. Appoint to the concept of women’s agency, this paper will discusses about a movie with title Birds of Prey written by female writer, Christina Hodson. The data of this paper taken by analysis on the movie directly, concerning the cinematography, and consideration of each scene and script. Brids of Prey casted by many female characters that come up as the main and supporting characters. Main character of this movie is exercise her agency in her environment is hardly to fight, and the character of hers already labelled as a rebellion person in her society so she has to fight for her agency. For another female characters, the way of they fight for their agency are dissimilar to each other yet with the same case they face. The result is those female character in movie Birds of Prey are joining hands to fight altogether their agency and show that women are not that weak. Keywords: Agency, Feminist, Cinematography